Navigating Diversity: Exploring Inclusive Citicenship and Recognition of Minority Rights in the Indonesian Context - Ikhsan, M. Alifudin; Zakiyah, Millatuz; Husniyah, Af'idatul; Arawindha, Ucca; Marzuki, Marzuki; Suharno, Suharno (Universitas Negeri Malang, 2024)
This study aims to describe the concept of inclusive citizenship as a requirement to become a good citizen and to analyze the implementation of inclusive citizenship in an effort to fulfill minority rights. study uses a literature study method through several stages,from problem identification to synthesis of findings. The study results indicate that inclusive citizenship is one of the requirements for becoming a good citizen, emphasizing the relationship between citizens and the state to uphold recognition of the importance of institutional multiculturalism and minority rights. The implementation of inclusive citizenship to fulfill minority rights is faced with quite significant challenges and obstacles. Challenges in implementing inclusive citizenship are related to socio-cultural values that tend to be exclusive. Obstacles to implementing inclusive citizenship are the existence of societal stereotypes, discrimination, and the lack of public understanding of diversity.